Synthesis of Nucleo Aminooxy Acid Derivatives - Noel, Olivier; Xie, Juan (Synthesis, 2013)
Nucleobase-functionalized peptides have attracted increasing interest because of their well-ordered secondary structures and stability toward enzymatic degradations. We have designed and synthesized nucleo aminooxy acids as novel building blocks for nucleopeptides. Four nucleo aminooxy acid derivatives with cytosine or thymine in the side chain linked by an amide or a triazole moiety have been synthesized from l-serine.
Keywords: nucleo aminooxy acids; nucleopeptides; N-oxy nucleopeptides; cytosine; thymine; amides; triazoles; l-serine; eliminations